Risk factors for the development of ocular graft-versus-host disease (GVHD) dry eye syndrome in patients with chronic GVHD. Issue 11 (6th May 2015) - Wang, Jay Ching Chieh; Teichman, Joshua C; Mustafa, Majd; O'Donnell, Heather; Broady, Raewyn; Yeung, Sonia N
Abstract : Background: To investigate the factors associated with the development of ocular graft-versus-host disease (oGVHD) dry eye syndrome (DES) in patients with chronic GVHD (cGVHD) after receiving allogenic haematopoietic stem cell transplantation (AHSCT) Methods: A retrospective chart review of patients receiving AHSCT between 1998 and 2013 at the Bone Marrow Transplant Unit of the British Columbia Cancer Agency was carried out. Demographic and clinical data from both donors and recipients were obtained. The diagnostic criteria for the development of oGVHD DES from the National Institutes of Health were used to identify patients with the disease. Descriptive and inferential statistics were carried out. Results: A total of 146 patients with a median follow-up time of 24.0 months (range 11.3–249.7 months) were included in this study. Sixty-six (45.2%) patients were women. Seventy-seven (52.7%) patients had oGVHD DES. The median age of patients was 57 years (range 25–71 years). Compared with other ethnicities, Caucasian patients were less likely to develop oGVHD DES, with an OR of 0.29 (p=0.01). Patients who received a transplant from Epstein–Barr-positive donors had a higher prevalence of oGVHD DES (OR=4.39, p=0.01). This was also found in patients with the following systemic involvement of cGVHD: grade 1–3 cGVHD skin involvement (OR=1.57, p=0.01), oral involvement (OR=2.51, p=0.01) and liver involvement (p=0.04). Patients with grade 2–3 overall cGVHD were also more susceptible to oGVHD DES (OR=2.72, p<0.001). Conclusions: This study identified risk factors associated with a higher prevalence of oGVHD DES in post-AHSCT patients with cGVHD.